DIGITAL SUBTRACTION PHLEBOGRAPHY USING A “HOMEMADE” CARBON DIOXIDE DELIVERY SYSTEM - Ferreira, Joana (2018)
Introduction and objectives: Carbon dioxide (CO2) is a non-nephrotoxic contrast media. Due its advantages and to the lack of dedicated CO2 delivery system in some hospitals, homemade CO2 delivery systems have been developed in several institutions. The authors describe a CO2 “homemade” delivery system developed with resources available in the author’s hospital and present the preliminary results of its application. Material and Methods: A disposable aluminum cylinder containing 99.9% pure CO2 is connected to a laparoscopic tower. In the connecting tube, between the laparoscopic tower and a 50 mL syringe there is a filter. The syringe is connected to the connecting tube and to the diagnostic catheter with three three-way stopcock fixed together in line. Results: From October 2015 and February 2016, six phlebographies, in four patients with dysfunctional arteriovenous fistulas were performed. The procedures were: angioplasty at the cephalic arch stenosis (one intervention); angioplasty at multiple focal stenosis at the basilic vein (two interventions) and angioplasty at multiple focal stenosis at the basilic vein (three interventions). A case of cerebral gas embolism was recorded. Conclusion: The delivery system we use is useful to maintain the patency of arteriovenous fistula in pre-dialysis patient. However, CO2 injection rate should be reduced, to avoid cerebral gas embolism.